Ortodoksja jako droga twórczego rozwoju dziecka w "Panarionie" Epifaniusza z Salaminy - Gilski, Marek; Wysocki, Marcin (Vox Patrum, 2022)
The article deals with the issue of a child in Epiphanius of Salamis’ Panarion. The paper consists of three main parts: the first shows the meaning of childhood according to Epiphanius, the second presents the negative attitudes of heretics towards children, and in the last the Christ’s childhood is analysed. As a result of analysis we can state that according to Epiphanius 1. Childhood is an important stage in the life of every person and the human kind, and should be creatively developed. It is a mistake to try to distance oneself from the values obtained in childhood; 2. In Panarion there is no details of the childhood of heresiarchs with few exceptions; 3. The image of a child closely related to orthodox theology emerges from the pages of the catalogue of heresies. Negative attitudes towards children are related to the activities of heretics; 4. Panarion is a proof that in the first centuries, in the time of persecution and the rise of various heresies, many Christian families failed in religious education as their children did not persist in the orthodox faith in which they were raised.